DEVELOPMENT OF A REVERSED PHASE - HPLC METHOD FOR DETERMINATION OF MELOXICAM IN TABLET FORMULATION AND HUMAN SERUM - Shlear H. Hasan; Nabeel S. Othman; Kafia M. Surchi (European Scientific Journal, ESJ, 2015)
Developing a simple, economic, sensitive and rapid isocratic RPHPLC method for determination of meloxicam (MX) in bulk drug, tablet formulation and human serum. The retention time observed for meloxicam was just 2.35 minutes using C18 column (150 x 3.0 mm, 5 μm) with a mobile phase consisting of acetonitrile: 0.2% formic acid (70:30 v/v%) at a flow rate of 1 ml/min with UV detector set at 355 nm. Linearity in concentration range of 0.05 – 50 µg/ml, with coefficient of determination, R² = 0.9956; slope= 25464 and intercept= -8872. The limit of detection and the limit of quantification were found to be 0.011 and 0.173 μg/ml, respectively. The precision and accuracy of method were checked by calculating RSD% and relative error E%, which were found to be reasonable. A RSD% (0.06 and 0.021%) for marketed brand and human serum, respectively and E% (0.64 and -0.47 %) for marketed brand and human serum, respectively. The method was found to be applicable for the analysis of MX in bulk, tablet formulation and human serum